Associations between galectin-1, left ventricular diastolic dysfunction, and heart failure with preserved ejection fraction. Issue 3 (March 2022) - Tsai, Yi-Lin; Chou, Ruey-Hsing; Lu, Ya-Wen; Chang, Chun-Chin; Kuo, Chin-Sung; Huang, Po-Hsun; Chen, Jaw-Wen; Lin, Shing-Jong
Abstract: Background: : Galectin-1 is a glycan-binding protein with broad anti-inflammatory properties. Left ventricular diastolic dysfunction (DD) is associated with heart failure and mortality. The pathophysiology of DD is complex and our study aimed to investigate the associations between serum galectin-1 level, DD, and heart failure with preserved ejection fraction (HFpEF). Methods: : Patients with symptoms of angina pectoris were enrolled. Serum galectin-1 levels and echocardiography were assessed. The study endpoint was a composite of all-cause mortality or new-onset HFpEF. Results: : In total, 258 patients were enrolled (63% male; mean age 68±12 years) and grouped into tertiles based on galectin-1 levels. Patients in the highest galectin-1 group had increased left ventricular mass indexes, left atrial diameters, and prevalence of DD compared to those in the lower tertiles (all p <0.05). Moreover, elevated galectin-1 levels were significantly associated with the composite endpoint ( p =0.039). After adjusting for confounding factors, high galectin-1 levels remained significantly associated with DD (odds ratio 2.44, p =0.005). The Kaplan-Meier analysis revealed patients in the highest galectin-1 group had lowest cumulative survival of composite endpoint (log rank p =0.043). Conclusions: : Elevated serum galectin-1 levels were associated with DD and the composite endpoint of all-cause mortality and incident HFpEF. Graphical abstract: Image, graphical abstract